The Impact of Dividends on Future Earnings : Evidence from Malaysian Public Listed Companies - Chin, Chee Ling; Jais, Mohamad; Salawati, Sahari (HRMARS, 2023)
Dividends are not only a means of regular income but also an important input in the valuation of firm through the information content of dividends. This study investigates the impact of dividends on future earnings among Malaysian public listed companies from 2000 to 2020 with panel data analysis. Overall, the results show insignificant relationships between dividends and future firm performance, which refute the information content hypothesis of the signaling theory. However, sensitivity analysis among subsamples with large market capitalization, high payout frequency and those that also pursue share buyback programs portray positive and significant firm performance in the first year subsequent to dividend payment. Therefore, it is suggested that future research may examine the impacts of dividends on future firm performance over a longer period of time that exceeds one year.